Activation of the Transducers of Unfolded Protein Response in Plants - Nawkar, Ganesh M.; Lee, Eun Seon; Shelake, Rahul M.; Park, Joung Hun; Ryu, Seoung Woo; Kang, Chang Ho; Lee, Sang Yeol (Frontiers in Plant Science, 2018)
Maintenance of the endoplasmic reticulum (ER)-homeostasis ensures the balance between the nascent proteins loading and their secretion. Certain developmental conditions or environmental stressors affect protein folding causing ER stress. The resultant ER stress is mitigated by upregulating a set of stress-responsive genes in the nucleus, commonly known as unfolded protein response (UPR). In plants, UPR is mediated by two major pathways; one by proteolytic processing of bZIP17/28 and the other includes IRE1-mediated splicing of bZIP60 mRNA. Lately, the plant-specific NAC transcription factors have also shown to be involved in UPR regulation. The molecular mechanisms activating plant-UPR transducers have just begun to be unveiled. In this review, we focused on important structural features involved in the activation of UPR transducers such as bZIP17/28/60, IRE1, BAG7, and NAC017/062/089/103. Also, we discussed the activation of UPR pathways including BAG7-bZIP28 and IRE1-bZIP60 in detail together with the NAC-TFs which adds new paradigm to the plant UPR.